2015
DOI: 10.1016/j.vaccine.2015.06.076
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection in HIV-exposed infants in the Western Cape, South Africa

Abstract: Hepatitis B virus infection (HBV) is a significant public health problem in sub-Saharan Africa. Universal infant vaccination with the hepatitis B (HB) vaccine has been implemented within the South African Expanded Programme of Immunization since April 1995 with concomitant reduction in HBV infection in children. However, the first vaccine dose is only administered at six weeks of age. This delay may lead to a failure to reduce the risk of perinatal HBV transmission to infants born to HIV/HBV co-infected women,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…However, there is undoubtedly a need for ongoing vigilance and efforts to reduce transmission still further. Together with the recent results from the Western Cape [4], these studies suggest that strategies to prevent mother to child HBV transmission have been successful, but need to remain an important focus. Furthermore, there are ongoing challenges; HBV immunisation is not routinely available for adults in the public sector (though should be available for those at risk), and availability of the new hexavalent vaccine has been problematic.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, there is undoubtedly a need for ongoing vigilance and efforts to reduce transmission still further. Together with the recent results from the Western Cape [4], these studies suggest that strategies to prevent mother to child HBV transmission have been successful, but need to remain an important focus. Furthermore, there are ongoing challenges; HBV immunisation is not routinely available for adults in the public sector (though should be available for those at risk), and availability of the new hexavalent vaccine has been problematic.…”
Section: Discussionmentioning
confidence: 87%
“…Published around the same time, a study from the Western Cape reports 0.4% prevalence of HBV in HIV exposed-uninfected (HEU) infants, all of whom were HBV-immunised according to local policy [4]. Together, these data highlight that chronic HBV is a persistent problem in South African adults, irrespective of HIV status, and that infants remain vulnerable to vertical acquisition of HBV infection before receiving their first dose of vaccine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 In the era of the South African HIV epidemic, a study conducted in the Western Cape in 2011 found the prevalence of HBV amongst HIV-exposed infants to be 0.4%. 14 The rate of HIV/HBV co-infection amongst infants and children remains poorly reported compared with reports of high exposure to HBV in HIV-infected pregnant women. 9 …”
Section: Introductionmentioning
confidence: 99%